Single CT colonography versus three rounds of faecal immunochemical test for population-based screening of colorectal cancer (SAVE): a randomised controlled trial. (November 2022) - Sali, Lapo; Ventura, Leonardo; Mascalchi, Mario; Falchini, Massimo; Mallardi, Beatrice; Carozzi, Francesca; Milani, Stefano; Zappa, Marco; Grazzini, Grazia; Mantellini, Paola
Summary: Background: Colorectal cancer screening is recommended for people aged 50–75 years, but the optimal screening test and strategy are not established. We aimed to compare single CT colonography versus three faecal immunochemical test (FIT) rounds for population-based screening of colorectal cancer. Methods: This randomised controlled trial was done in Florence, Italy. Adults aged 54–65 years, never screened for colorectal cancer, were randomly assigned (1:2) by simple randomisation and invited by post to either a single CT colonography (CT colonography group) or three FIT rounds (FIT group; each round was done 2 years apart). Exclusion criteria included previous colorectal cancer, advanced adenoma, or inflammatory bowel disease, colonoscopy within the last 5 years or FIT within the last 2 years, and severe medical conditions. Participants who had a colonic mass or at least one polyp of 6 mm or more in diameter in the CT colonography group and those who had at least 20 μg haemoglobin per g faeces in the FIT group were referred for work-up optical colonoscopy. The primary outcome was detection rate for advanced neoplasia. Outcomes were assessed in the modified intention-to-screen and per-protocol populations. The trial is registered with ClinicalTrials.gov, NCT01651624 . Findings: From Dec 12, 2012, to March 5, 2018, 14 981 adults were randomised and invited to screening interventions. 5242 (35·0%) individuals (2809 [53·6%] women and 2433 [46·4%] men) were assigned to the CT colonography group and 9739 (65·0%) individuals (5208 [53·5%] women and 4531 [46·5%] men) were assigned to the FIT group. Participation in the screening intervention was lower in the CT colonography group (1286 [26·7%] of the 4825 eligible invitees) than it was for the FIT group (6027 [64·9%] of the 9288 eligible invitees took part in at least one screening round, 4573 [49·2%] in at least two rounds, and 3105 [33·4%] in all three rounds). The detection rate for advanced neoplasia of CT colonography was significantly lower than the detection rate after three FIT rounds (1·4% [95% CI 1·1–1·8] vs 2·0% [1·7–2·3]; p=0·0094) in the modified intention-to-screen analysis, but the detection rate was significantly higher in the CT colonography group than in the FIT group (5·2% [95% CI 4·1–6·6] vs 3·1% [2·7–3·6]; p=0·0002]) in the per-protocol analysis. Referral rate to work-up optical colonoscopy (the secondary outcome of the trial) was significantly lower for the CT colonography group than for the FIT group after three FIT rounds (2·7% [95% CI 2·2–3·1] vs 7·5% [7·0–8·1]; p<0·0001) in the modified intention-to-screen analysis, whereas no significant difference was observed in the per-protocol analysis (10·0% [8·4–11·8] vs 11·6% [10·8–12·4]). No major complications were observed in the CT colonography group after screening and work-up optical colonoscopy, whereas three cases of bleeding were reported in the FIT group after work-up optical colonoscopy (two after the first FIT and one after the second FIT). Interpretation: Greater participation makes FIT more efficient than single CT colonography for detection of advanced neoplasia in population screening for colorectal cancer. Nonetheless, higher detection rate in participants and fewer work-up colonoscopies are possible advantages of CT colonography as a screening tool, which might deserve consideration in future trials. Funding: Government of Tuscany and Cassa di Risparmio di Firenze Foundation. Translation: For the Italian translation of the abstract see Supplementary Materials section.